Pengaruh Reward dan Punishment Terhadap Motivasi Belajar Siswa Kelas IV A SDN Merak I pada Mata Pelajaran IPS - Melinda, Ima (International Journal of Elementary Education, 2018)
This study aims to determine whether there is a significant influence between the provision of rewards and pusnishment to the motivation of fourth grade students of SDN Merak I Tangerang and how big the contribution of reward and punishment influence on learning motivation. This research is a quantitative research. The population of this research is the fourth grade students of SDN Merak 1 Tangerang, which are 38 students. Sampling Technique Saturated .. Data collection is done by using questionnaire method (questionnaire). Data Research Results indicate that there is a significant influence between the discipline of learning on the motivation of learning grade IV This is obtained through the calculation of the test analysis with thitung tribe for 9.096 while the ttabel of 0.3932. Because thitung (9.096)> ttable (0.3932) and with significance test is known significance value 0,000 <0,05 then Ho is rejected and Ha accepted, which means there is positive and significant influence between reward and punishment variable on student learning motivation Amount of donation the influence given by X (reward and punishment) on Y (Student Motivation Motivation) is 82.1%, which means that the predictors of reward and punishment have influence on student learning motivation of 81,2% and the rest 18,8% influenced by other variables that are not examined in this study.